Diego Maradona: mito, héroe, símbolo de la subalternidad - Pablo Alabarces (SHARE Press, 2022)
The death of Argentine football player Diego Maradona on November 25, 2020 caused huge manifestations of public pain. At the same time, it unleashed intense journalistic coverage, which abused words such as myth, symbol, hero, idol and identity. The key question revolved around how far Maradona, an unrivaled athlete and simultaneously a conflictive public figure, for his personal conduct (including sports convictions and criminal cases for drug use) and for his political positions linked to left-wing populism, it could be considered a symbol of a presumed national identity. The work proposes to work on these categories, in the context of three decades of research on the relationship between sport and identities, as well as in relation to some hypotheses about subaltern voices in the contemporary scene.